(untitled) (Castilla. Estudios de Literatura, 2020)
Book Review of Illness and Literatura: Between Inspiration and Imbalance (Kassel, Reichenbergr, 2020) of Julie Botteron y Cipriano López Lorenzo (coords.) This review analyzes the book entitled Illness and literature: between inspiration and imbalance, a volume coordinated by Julie Botteron and Cipriano López Lorenzo on the occasion of the congress held in June 2018 by the Université de Neuchâtel. The work compiles fifteen of the contributions that took place there, which address, from different perspectives and from different texts, the relationships that can be established between the disease and literature.